Implementation of Pancasila Values as a Humanistic Legal Foundation for National Character (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
In Indonesia, the existing legal foundation is deeply rooted in the principle of Bhinneka Tunggal Ika, meaning “Unity in Diversity.” This philosophy emphasizes tolerance and harmony among diverse ethnic, cultural, and religious backgrounds. Within this principle, Pancasila stands as the fundamental legal and philosophical charter of the Indonesian state. Pancasila consists of five interrelated principles: the value of religiosity in the first principle, humanitarianism in the second, unity in the third, democracy in the fourth, and social justice in the fifth. These principles not only provide a legal framework but also act as a moral compass for the development of national character. The implementation of Pancasila values is crucial in shaping a society that respects human dignity, justice, and equality. The first principle emphasizes belief in God, encouraging moral responsibility and ethical behavior in personal and public life. The second principle underlines humanitarianism, which promotes empathy and respect for human rights. The third principle stresses national unity as a foundation for overcoming divisions and fostering solidarity. The fourth principle highlights democracy, ensuring that decision-making processes respect participation, consensus, and justice. Finally, the fifth principle, social justice, calls for equality and fairness in all aspects of society. In the era of globalization, where various ideologies and cultural influences intersect, the values of Pancasila remain relevant as a guiding philosophy for education, governance, and national development. It is not merely a static doctrine but a dynamic framework that adapts to societal changes while maintaining Indonesia’s identity. Thought, therefore, can be seen as an effort to deeply reflect on and internalize the values of Pancasila, then translate them into concepts, practices, and theories applicable to contemporary challenges. Strengthening the understanding and practice of Pancasila is vital for ensuring that Indonesia’s national character continues to reflect unity, diversity, and humanity in facing global complexities.